From Local Concerns to Global Challenges: Continuity and Change in Sub-state “Green Nationalism” - Hau, Mark F. (Frontiers in Political Science, 2022)
Issues related to anthropogenic climate change such as global warming, fossil fuel emissions, and renewable energy have emerged as some of the most important and pertinent political questions today. While the role of the state in the Anthropocene has been explored in academia, there is a severe dearth of research on the relationship between climate change and nationalism, especially at the sub-state level. This paper builds on the concept of “green nationalism” among sub-state nationalist parties in European minority nations. Using a multimodal analysis of selected European Free Alliance (EFA) campaign posters from the past 30 years, the article explores an extensive “frame bridging” where minority nationalist political actors actively seek to link environmental issues to autonomy. Although there is an apparent continuity in minority nationalist support for green policies, earlier initiatives focused on preservation of local territory while EFA parties today frame climate change as a global challenge that requires local solutions, which only they can provide. The frame bridging between territorial belonging and progressive politics has lead to the emergence of an environmentally focused, minority nationalist agenda that advocates for autonomy in order to enact more ambitious green policies, or “green nationalism”. This shows that nationalism in the right ideological environment can be a foundation for climate action, as minority nationalist actors base their environmentally focused agenda to address the global climate crisis precisely on their nationalist ideology.